Logistics Risk Management at CV. Protani in Palu City - Yusman, Zaskia Zahrani; Hadi, Suryadi; Kaseng, Saharuddin; Dwiwijaya, Kadek Agus (Dinasti Publisher, 2025)
This study examines logistics risk management at CV. Protani in Palu City using a descriptive qualitative approach. The study aims to identify, analyze, and evaluate logistics risks within CV. Protani. The research methods employed include direct observation and interviews with the company owner, administrator, and transportation drivers involved in the company's logistics activities. The results reveal a total of 11 risks identified in the logistics activities of CV. Protani. These risks stem from both internal and external factors. The analysis indicates that 5 risks have moderate impacts, 4 risks have high impacts, and 2 risks have very high impacts on the company. Therefore, risks with high and very high impacts require mitigation efforts to reduce their effects and likelihood of occurrence, thereby minimizing potential losses in the company’s logistics activities.